How Diverse Is Your Universe? An Activity for Students to Reflect on Ethnoracial Diversity During Orientation - Tahira J. West; Kimberly Loomer; Tasha R. Wyatt (Association of American Medical Colleges, 2019)
Introduction Physicians' unconscious biases have been linked to health disparities within ethnic and racially diverse communities. Addressing these unconscious biases is difficult but may be ameliorated by raising individuals' awareness of the ethnoracial makeup of their personal and professional networks and reflecting on whether it needs to be expanded while in medical school. Methods First- and second-year students were provided with an overview of the ethnoracial makeup of individuals within the state, community, and medical school as a means to reflect on the ethnoracial makeup of their future patient population. Following this overview, students engaged in an activity adapted from the University of Houston, which allowed them to visually represent the ethnoracial diversity within their networks. Written reflections on the adapted activity were collected, analyzed using manifest content analysis, and reported according to themes. Results The results indicated that the activity was valuable in helping students visualize their current exposure to ethnoracially diverse individuals (143 of 357 responses [40%]) and reflect on their need to expand the level of ethnoracial diversity in their lives (47 of 357 responses [13%]). Additionally, students provided comments to help improve the activity when used in another institution. Discussion Assisting students in raising their awareness of the ethnoracial diversity in their personal and professional networks is a step toward addressing the unconscious biases that emerge in physicians while in clinical practice. This activity, designed to raise students' awareness of ethnoracial diversity, originated in Augusta, Georgia, but can be adapted to any state.